1971
DOI: 10.1128/jb.108.2.817-823.1971
|View full text |Cite
|
Sign up to set email alerts
|

γ-Aminobutyric Acid as a Required Germinant for Mutant Spores of Bacillus megaterium

Abstract: Germinated spores of Bacillus megaterium QM B1551 were irradiated with ultraviolet light, and spore-forming survivors were screened for germination requirements. Spore strains which failed to germinate in a variety of defined solutions germinative for spores of the parent strain were obtained. Mutant spores germinated readily in solutions containing yeast extract or one of numerous complex preparations. y-Aminobutyric acid, obtained from yeast extract by column chromatography, was shown to be required for germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

1972
1972
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Strong support for the role of metabolism in triggering germination came from studies on glutamate degradation during germination of B. megaterium QMB 1551 (Foerster, 1972), in which it was shown that 50% of the glutamate pool of the spore was degraded via 4-aminobutyrate within 30s of exposure to germinants. The role of 4-aminobutyrate and the enzyme producing it (glutamate decarboxylase, EC 4.1.1.15) was further emphasized by studies on a mutant requiring 4-aminobutyrate for germination (Foerster, 1971;Foerster & Foerster, 1973).…”
mentioning
confidence: 99%
“…Strong support for the role of metabolism in triggering germination came from studies on glutamate degradation during germination of B. megaterium QMB 1551 (Foerster, 1972), in which it was shown that 50% of the glutamate pool of the spore was degraded via 4-aminobutyrate within 30s of exposure to germinants. The role of 4-aminobutyrate and the enzyme producing it (glutamate decarboxylase, EC 4.1.1.15) was further emphasized by studies on a mutant requiring 4-aminobutyrate for germination (Foerster, 1971;Foerster & Foerster, 1973).…”
mentioning
confidence: 99%
“…Residual pool "C-glutamic acid in germinating spores of strain yOG5. Strong presumptive evidence in support of endogenous glutamic acid as a potentially important metabolite in spore germination derives a priori from the fact that mutant spore strains, having a specific requirement for exogenous y-aminobutyric acid, can be obtained (3). A requirement of y-aminobutyric acid by these strains for spore germination may result from their inability to metabolize (decarboxylate) endogenous glutamic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of spores. The medium, growth conditions, and the methods used in the preparation and storage of spore suspensions have been described (3). Techniques used in the preparation of "4C-labeled spores are described below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations